182 PULMONARY FUNCTION AND WEIGHT GAIN IN VERY LOW BIRTH WEIGHT INFANTS. (1st January 2005) - Hibbs, A. M.; Lorch, S. A.; DiFiore, J. M.; Martin, R. J.; Merrill, J. D.; Ballard, R. A.
Abstract : Background: Lung disease in very low borth weight (VLBW) infants is known to affect weight gain. We consider whether the results of a pulmonary function test (PFT) in the first weeks of life are associated with infants' weight at 36 weeks post-menstrual age (Wt36). Methods: We studied conventionally ventilated infants <32 weeks GA and a BW ≤1250g enrolled in the NO CLD multicenter randomized trial of inhaled nitric oxide who had a PFT performed prior to initiation of study drug. Infants could be enrolled between 7 and 21 days of age. PFTs were obtained with the CO2SMO plus! Respiratory Profile Monitor and Analysis Plus! Software. Dynamic compliance (Cdyn) and expiratory airway resistance (Rexp) were calculated via a least squares technique using a single compartment linear model. Linear regression models were generated to assess the association of Wt36 with Cdyn and Rexp after controlling for confounding factors including weight at the time of PFT. BW was not added to the regression models due to a high degree of colinearity with weight at the time of PFT. Results: 55 infants with mean GA of 25.4 wks (range 23-38) and BW of 737g (range 500-1105) had a PFT performed on a mean age of 15 days (range 7-21). Mean Cdyn was 0.39 cc/cmH2O (range 0.20-0.66), and Rexp 226 cm H20/L/sec (range 53-348). One infant died before reaching 36 weeks adjusted age and was excluded from further analysis. Mean Wt36 was 1847g (range 1267-2350). In univariate analysis, Cdyn was significantly (p≤0.001) associated with Wt36. When weight at the time of PFT was added to this model, the effect size on Cdyn dropped by 29%, but Cdyn remained significant (p=0.027). In contrast, Rexp, duration of parenteral nutrition, days until enteral feedings of 100kcal/kg were achieved, days on the ventilator, and ventilation status at 36 weeks were not significantly associated with Wt36 in univariate models. In a multivariate linear regression model (R2=0.55), Cdyn remained significant (coefficient 583 g/cc/cmH20, p=0.035) after controlling for weight at the time of PFT, GA, and duration of parenteral nutrition. GA and weight at the time of the PFT were significant in this model, but duration of parenteral nutrition was not. Conclusion: In VLBW infants, Cdyn is associated with Wt36. These results highlight the effect of lung disease on growth in VLBW infants, and may reflect work of breathing or overall severity of illness. Furthermore, they emphasize the relationship between early pulmonary status and outcome.